PEMBELAJARAN BERBASIS LITERASI DIGITAL UNTUK PENGUATAN MODERASI BERAGAMA (STUDI KASUS DI SMA NEGERI 2 SALATIGA) - Syaefudin Achmad (Journal of Research and Thought on Islamic Education (JRTIE), 2022)
This article aims to determine the process of implementing digital literacy based learning to streghthen religious moderation at SMA Negeri 2 Salatiga. The background of the writing of this article is cases of intolerance that still occur in Indonesia, even in schools. In fact, schools are educational institutions that are at the forefront of preventing radicalism and intolerance in schools. This research uses a qualitative approach, the type of field research, data collection techniques using observation, interviews, and documentation, data analysis techniques using data presentation, data reduction, and drawing conclusions. Digital literacy-based religious moderation learning at SMA Negeri 2 Salatiga was carried out in the form of an assignment to write in the form of personal experiences of associating with followers of other religions, attitudes towards the Republic of Indonesia, and about heroes. The result of this study can be a reference for schools at Indonesia in implementing digital literacy based learning to streghthen religious moderation. Keywords: Learning, Digital Literacy, Religious Moderation